Halophyte biorefinery for polyhydroxyalkanoates production from Ulva sp. Hydrolysate with Haloferax mediterranei in pneumatically agitated bioreactors and ultrasound harvesting. (January 2022) - Ghosh, Supratim; Coons, Jim; Yeager, Chris; Halley, Peter; Chemodanov, Alexander; Belgorodsky, Bogdan; Gozin, Michael; Chen, Guo-Qiang; Golberg, Alexander
Graphical abstract: Highlights: Application of extreme halophilic archaea for PHA production . Utilization of pneumatically agitated reactors for outdoor fermentation. Application of ultrasonic separation technology for harvesting of archaeal biomass. Value addition towards a halophilic biorefinery. Abstract: The present study tested the outdoor cultivation of Haloferax mediterranei for PHA production from green macroalgae Ulva sp. in pneumatically agitated bioreactors and applied ultrasonic separation for enhanced settling of archaeal cells. Scaled-up cultivation (40 L) yielded maximum biomass productivity of 50.1 ± 0.11 mg·L -1 ·h −1 with a PHA productivity of 27 ± 0.01 mg·L -1 ·h −1 and conversion yield of 0.107 g PHA per gram Ulva DW . The maximum mass fraction of PHA achieved in biomass was calculated to be 56% w/w. Ultrasonic harvesting of Hfx. mediterranei cells approached 30% removal at energy inputs around 7.8 kWh·m −3, and indicated no significant aggregation enhancement by Ca 2+ addition. Molecular weight analysis showed an increase in Polydispersity Index (PDI) when the corresponding air velocities were increased suggesting that the polymer was more homogeneous at lower mixing velocities. The current study demonstrated scalable processes for PHA production using Ulva sp. feedstock providing new technologies for halophilic biorefinery.